Studies in Qur’an and Hadith: The Formation of the Islamic Law of Inheritance by David S. Powers; Berkeley: University of California Press, 1986, 263 pp. (Appendices, Glossary Bibliography, Index and Tables). (American Journal of Islam and Society, 1989)
David S. Powers’ book, originally a doctoral dissertation submitted toPrinceton University, is a welcome addition to the already growing corpusof studies revising Joseph Schacht’s thesis that Islamic law did not exist duringthe lifetime of the Prophet. This is, however, not the central theme ofthe book. Powers contends that the Islamic law of inheritance is not identicalto the system of inheritance revealed to Prophet Muhammad and that theMuslim community is not in possession of the original reading and understandingof several Qur’anic verses and Prophetic hadith.The thesis presented in this book can be summarized as follows:Islamic law began to develop with Qur‘anic legislation which was moreclear and systematic on the subject of inheritance. In pre-Islamic Arabia theintergenemtional transmission of property was by seniority rather than by directdescent. The Qur’an introduced a new system of inheritance which reflecteda transition from tribalism to individualism, with more emphasis on the rightsof women to property. The author sees two systems of the law of inheritancein Islam:1) The proto-Islamic law of inheritance which existed only during2) Islamic law of inheritance, which exists as ‘ilm al-farii‘id.the lifetime of the Prophet; and,Powers contends that the proto-Islamic system was mainly testatory andthe property was distributed according to fixed shares only in the absenceof a will. Husband and wife, not being blood relatives, inherited as testatoryheirs.The author divides his dissertation into two parts. In the first part he dealswith the proto-Islamic, in the second with the Islamic system of inheritance.The first part proceeds by looking at the practice of bequest and testation inMakkah and Madinah in early Islam, giving special attention to the inheritancebetween husbands and wives, and the Qur’anic law of testation and intestacy.The second part proceeds by looking at socio-economic developmentsin the early period and contends that people in power manipulated the Qur‘anic ...